2017
DOI: 10.1038/srep45859
|View full text |Cite
|
Sign up to set email alerts
|

pH-Controlled Cerium Oxide Nanoparticle Inhibition of Both Gram-Positive and Gram-Negative Bacteria Growth

Abstract: Here, the antibacterial activity of dextran-coated nanoceria was examined against Pseudomonas aeruginosa and Staphylococcus epidermidis by varying the dose, the time of treatment, and the pH of the solution. Findings suggested that dextran-coated nanoceria particles were much more effective at killing P. aeruginosa and S. epidermidis at basic pH values (pH = 9) compared to acidic pH values (pH = 6) due to a smaller size and positive surface charge at pH 9. At pH 9, different particle concentrations did cause a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 62 publications
(86 reference statements)
4
83
0
Order By: Relevance
“…As discussed in the last section, the reversible conversion between Ce(III) and Ce(IV) is the cause of ROS generation. He et al [52] found a notable increase in the intracellular ROS level upon the exposure to 100 and 200 mg mL −1 CeO 2 NPs in normal saline (NS: 0.9% NaCl; pH 6.8) medium within 2 h. Alpaslan et al [56] reported that the quantity of generated ROS elevated in both Pseudomonas aeruginosa (P. aeruginosa) and…”
Section: Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed in the last section, the reversible conversion between Ce(III) and Ce(IV) is the cause of ROS generation. He et al [52] found a notable increase in the intracellular ROS level upon the exposure to 100 and 200 mg mL −1 CeO 2 NPs in normal saline (NS: 0.9% NaCl; pH 6.8) medium within 2 h. Alpaslan et al [56] reported that the quantity of generated ROS elevated in both Pseudomonas aeruginosa (P. aeruginosa) and…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The impact of dispersing medium (along with the pH) on the antibacterial behavior is essentially attributed to the electrostatic interaction, which means the acidity/basicity of the suspension will affect the surface charge on NPs, and finally lead to the variation of interaction between NPs and bacteria. Alpaslan et al [56] reported that the positive charged dextran-coated CeO 2 NPs in pH 9 medium had relatively stronger interaction with the bacterial membrane, whereas in pH 6 medium, the surface charge of NPs became negative (−8.75 mV) and led to the decrease of the antibacterial efficiency. This variation in surface charge can be measured by zeta potential (Fig.…”
Section: Dispersing Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their charged surface and high surface area, NPs tend to aggregate into clusters that can be several micrometers in diameter. 24 This is also the case with CeNPs. To solve this problem, polymer encapsulation of the CeNPs is an ideal method.…”
Section: Cerium Oxide Nps (Cenps) Overviewmentioning
confidence: 75%